2020
DOI: 10.3390/jcm9020372
|View full text |Cite
|
Sign up to set email alerts
|

Loss-of-Function Variants in Cytoskeletal Genes Are Associated with Early-Onset Atrial Fibrillation

Abstract: Atrial fibrillation (AF) is the most common cardiac arrhythmia, and it is associated with an increased risk of heart failure, stroke, dementia, and death. Recently, titin-truncating variants (TTNtv), which are predominantly associated with dilated cardiomyopathy (DCM), were associated with early-onset AF. Furthermore, genome-wide association studies (GWAS) associated AF with other structural genes. In this study, we investigated whether early-onset AF was associated with loss-of-function variants in DCM-associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 39 publications
0
25
0
1
Order By: Relevance
“…Recently, Vad et al identified six individuals with rare loss-of-function variants in three different DCM genes (DMD, PDLIM3, and FKTN), of which two variants were novel. These data suggest that rare loss-of-function variants in cytoskeletal genes previously associated with DCM may have a role in early-onset AF, perhaps through the development of an atrial cardiomyopathy [66].…”
Section: Cardiomyopathymentioning
confidence: 75%
“…Recently, Vad et al identified six individuals with rare loss-of-function variants in three different DCM genes (DMD, PDLIM3, and FKTN), of which two variants were novel. These data suggest that rare loss-of-function variants in cytoskeletal genes previously associated with DCM may have a role in early-onset AF, perhaps through the development of an atrial cardiomyopathy [66].…”
Section: Cardiomyopathymentioning
confidence: 75%
“… Wang et al (2019) found that polymorphisms in PDLIM3 gene increased risk of idiopathic dilated cardiomyopathy. Other studies indicated PDLIM3 was also correlated to hypertrophic cardiomyopathy ( Lopes et al, 2015 ; Bagnall, Yeates & Semsarian, 2010 ), atrial fibrillation ( Vad et al, 2020 ), myofibrillar myopathy ( Williams et al, 2021 ), the prognosis of hepatocellular carcinoma ( Wu et al, 2021 ), early regional metastasis of tongue cancer ( Lee et al, 2021 ), muscle-invasive bladder urothelial carcinoma ( Feng et al, 2020 ) and medulloblastoma ( Shou et al, 2015 ). It is the first time that PDLIM3 has been linked to endometriosis.…”
Section: Discussionmentioning
confidence: 99%
“…This is also consistent with the results for expression of circulating microRNA profiles in post-stroke patients with early onset of PSD and for target genes of these miRNAs that were found to have been enriched with respect to MAPK-related signaling pathways (Zhang et al, 2016 ). Accumulating evidence has also indicated that genetic variation in 3′-UTR contributes to the etiology of human diseases (Latini et al, 2017 ; Wigner et al, 2019 ; Vad et al, 2020 ). In recent years, miRSNPs have been recognized as potential genetic risk factors that have been rapidly identified and investigated.…”
Section: Discussionmentioning
confidence: 99%